Chronic heat stress induces the expression of HSP genes in the retina of chickens (Gallus gallus) - Bastaki, Nasmah K.; Albarjas, Taybha A.; Almoosa, Fatma A.; Al-Adsani, Amani M. (Frontiers in Genetics, 2023)
Chronic heat stress during summer is a major challenge imposed by global warming. Chickens are more sensitive to heat stress than mammals because they lack sweat glands. Thus, chickens are more susceptible to heat stress during summer than other seasons. Induction of heat shock protein (HSP) genes is one of the primary defense mechanisms against heat stress. Tissue-specific responses exhibited by different classes of HSPs upon exposure to heat stress have been reported previously in different tissues including the heart, kidney, intestine, blood, and muscle, but not in the retina. Therefore, this study aimed to investigate the expression levels of HSP27, HSP40, HSP60, HSP70, and HSP90 in the retina under chronic heat stress. This study was conducted during the summers of 2020 and 2021 in Kuwait. Chickens (Gallus gallus) were divided into control and heat-treated groups and sacrificed at different developmental stages. Retinas were extracted and analyzed by using Real Time quantitative Polymerase Chain Reaction (RT-qPCR). Our results from the summer of 2021 were similar to that from the summer of 2020, regardless of whether GAPDH or RPL5 was used as a gene normalizer. All five HSP genes were upregulated in the retina of 21-day-old heat-treated chickens and stayed upregulated until 35 days of age, with the exception of HSP40, which was downregulated. The addition of two more developmental stages in the summer of 2021 showed that at 14 days, all HSP genes were upregulated in the retina of heat-treated chickens. In contrast, at 28 days, HSP27 and HSP40 were downregulated, whereas HSP60, HSP70, and HSP90 were upregulated. Furthermore, our results showed that under chronic heat stress, the highest upregulation of HSP genes was seen at the earliest developmental stages. To the best of our knowledge, this is the first study to report the expression levels of HSP27, HSP40, HSP60, HSP70, and HSP90 in the retina under chronic heat stress. Some of our results match the previously reported expression levels of some HSPs in other tissues under heat stress. These results suggest that HSP gene expression can be used as a biomarker for chronic heat stress in the retina.